African socialism; or, the search for an indigenous model of economic development?. Issue 1 (2nd January 2018) - Akyeampong, Emmanuel
ABSTRACT: Ralph Austen in African Economic History (1987) noted how few African countries explicitly choose capitalism on independence, and for those who did it was a default model or a residual pattern. 'African socialism' was popular in the early decades of independence and pursued by several countries, including Ghana, Guinea, Senegal and Tanzania, the cases considered in this paper. The term had multiple meanings, and its advocates were quick to stress that they were not communist, and some said they were not even Marxist. This paper explores the argument that African socialism was a search for an indigenous model of economic development for a generation that was justifiably ambivalent about capitalism, but wary of being put in the communist camp in the Cold War era. Importantly, advocates of African socialism often proposed bold and transformative visions for their countries. These visions might be worth revisiting, devoid of the paradigm of socialism.